2020
DOI: 10.1177/0265407520933002
|View full text |Cite
|
Sign up to set email alerts
|

“We talked about our hookups”: A diary study of sexual communication among U.S. college women

Abstract: For many young women, college is a time of major changes in sexual behavior and attitudes, driven in part by their social environment. Yet little is known about how young women actually talk about sex day-to-day. To understand daily sexual communication, 96 U.S. college students who identify as women kept a sexual communication diary for 7 days, generating 1,211 records. A content analysis revealed that women talked about sex an average of 13 times per week. Most conversations were with friends, face-to-face, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…This finding shows how widespread the presence of sex, sexuality or sexual relations is, whether formally or informally, in our sample. This fact was studied a few years ago in the United Kingdom, when it was observed that female students talked about sex about 13 times a day [29].…”
Section: Discussionmentioning
confidence: 99%
“…This finding shows how widespread the presence of sex, sexuality or sexual relations is, whether formally or informally, in our sample. This fact was studied a few years ago in the United Kingdom, when it was observed that female students talked about sex about 13 times a day [29].…”
Section: Discussionmentioning
confidence: 99%